Examination of Community Participation of Adults With Disabilities: Comparing Age and Disability Onset. (December 2019) - Dashner, Jessica; Espin-Tello, Sandra Martina; Snyder, Makenna; Hollingsworth, Holly; Keglovits, Marian; Campbell, Margaret L.; Putnam, Michelle; Stark, Susan
Objective: Explore community participation between adults with disabilities ⩽50 and >50 years and between early-(⩽40) and late-(>40) onset disability.Method: A survey examining participation was conducted with a national convenience sample of 692 community-dwelling adults with disabilities.Results: Participants ⩽50 reported presence of more ( p < .05) environmental supports for work/volunteer/education and use of transportation. Participants >50 had higher ( p < .01) visits to pharmacies; higher ( p < .05) evaluative quality of participation (EQOP) at gas stations, exercise facilities, beauty salons/barbers, and use of transportation ( p < .01); and more difficulty participating without assistance at grocery stores ( p < .05) and gas stations ( p < .01). The early-onset group reported higher ( p < .05) EQOP at work/volunteer/education and homes of family/friends. The late-onset group reported higher ( p < .01) EQOP at exercise facilities; more ( p < .05) environmental supports at pharmacies, restaurants, grocery stores ( p < .01), doctors' offices ( p ⩽ .01), and beauty salons/barbers ( p < .01); greater ( p < .01) influence of pain/fatigue; and more difficulty without assistance at grocery stores ( p < .05) and gas stations ( p < .01).Discussion: Understanding these differences can improve interventions to support community participation of individuals aging with disabilities.